Representations and transformations for multi-dimensional systems - Simon J. McInerney (1999)
Multi-dimensional (n-D) systems can be described by matrices whose elements are polynomial in more than one indeterminate. These systems arise in the study of partial differential equations and delay differential equations for example, and have attracted great interest over recent years. Many of the available results have been developed by generalising the corresponding results from the well known 1-D theory. However, this is not always the best approach since there are many differences between 1-D, 2-D and n-D (n>2) polynomial matrices. This is due mainly to the underlying polynomial ring structure. [Continues.]